Impact of firms’ life-cycle on conservatism: the Malaysian evidence - Abdullah, Asna Atqa; Mohd Saleh, Norman (Elsevier, 2014)
The aim for this paper is to examine the impact of life-cycle attributes of firms on conservatism. This timely loss recognition attribute of earnings has been proven theoretically and empirically to benefit users of accounting information by addressing moral hazards in the economy, and constraining managerial opportunistic behaviour caused by asymmetric information. Using data from 1995 to 2010, the findings show that impacts of conservatism level using Khan and Watts (2009)’s C_score measure differ significantly through-out the life-cycle stages of firms.